On-the-job training effectiveness in business education: An evaluation of host training establishments in Nueva Ecija, Philippines - Natividad , Nestor Dela Cruz (Journal of Education and e-Learning Research, 2025)
This study assessed the effectiveness of on-the-job training (OJT) among BSBA–Marketing Management trainees at Nueva Ecija University of Science and Technology, Atate Campus. Guided by Memoranda of Understanding with Host Training Establishments (HTEs), four dimensions were examined: Supervision and Mentoring (SM), Learning Opportunities (LEO), Work Environment and Health Safety (WEHS), and Communication and Monitoring (CM). Using total enumeration, 59 students from the Classes of 2024 and 2025 were surveyed across government, retail, and service organizations in Nueva Ecija. Data were analyzed in JAMOVI using descriptive statistics, ANOVA, and Pearson correlation. Male trainees rated their experiences more positively than females, particularly on WEHS. No significant differences emerged by graduation year or organization type, though service-sector HTEs received slightly lower CM ratings. ANOVA revealed no significant group differences; however, correlations indicated strong positive associations among dimensions, notably between SM and CM (r = .810, p < .001). The findings support that integrated, well-structured programs enhance OJT outcomes and recommend continuing training on communication, supervision, and workplace safety, with emphasis on service settings, and consistent practice thereafter.